(untitled) (Bangladesh Journal of Medicine, 2015)
The renin-angiotensin system (RAS) or the renin-angiotensin-aldosterone system (RAAS) is a major endocrine/ paracrine system that regulates blood pressure (BP) via angiotensin release as well as fluid and electrolyte homeostasis via aldosterone release. RAAS should be constantly suppressed and any degree of activity may lead to hypertension (HTN) and associated target organ damage. Activation of the RAAS in the pathogenesis of hypertension, cardiovascular disease(CVD) and renal disease is well documented. Also benefits of inhibition of RAAS, as an effective way to intervene in the pathogenesis of HTN, CVD and chronic renal failure(CRF) has been well recognized. Inhibition of renin activity and the blockage of RAAS cascade at its primary steps, has long been proposed as the optimal means of RAAS inhibition. Renin inhibitor provides more effective means of RAAS Inhibition. Aliskiren is the first in a new class of orally active, non-peptide, low molecular weight direct renin inhibitor (DRI) available for clinical use and potential new approach to the blockade of the RAAS. Bangladesh J Medicine Jan 2014; 25 (1) : 21-24